How Do Credit Risk and Liquidity Shape Bank Profitability? Evidence From Indonesia: Do Credit Risk and Liquidity Shape Bank Profitability? Evidence From Indonesia - Rahma Febrianti; Akhmad Ghozali (Jurnal Ecoment Global, 2026)
Objective: This study empirically examines the effects of credit risk, liquidity, and interest rates on banking profitability in Indonesia. Using Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), and interest rates as independent variables, and Return on Equity (ROE) as the profitability measure, the research employs panel data regression to enhance empirical understanding of profitability determinants and contribute to banking literature in developing countries Design/Methods/Approach: A quantitative explanatory approach is applied to analyze publicly listed commercial banks in Indonesia from 2019 to 2024. Secondary data from annual financial reports are used. Credit risk is measured by NPL, liquidity by LDR, and interest rates serve as independent variables, while ROE indicates profitability. Panel data regression captures variations across banks and over time to produce consistent empirical results. Findings: Results show that NPL has a significant negative impact on ROE. LDR negatively affects ROE but is statistically insignificant, indicating liquidity is not a primary profitability determinant. Interest rates positively and significantly influence ROE, highlighting the crucial role of interest-based income in banking performance in Indonesia. Originality/Value: This research offers novelty by simultaneously testing credit risk, liquidity, and interest rates on banking profitability using panel data regression. It provides recent empirical evidence useful for risk management and policy formulation in the Indonesian banking sector. Practical/Policy implication: Findings suggest bank management should prioritize credit risk control to sustain profitability. The significant role of interest rates underscores the need for strategic responses to monetary policy changes. Policy implications call for regulatory support to ensure banking stability and sustainable risk management. Keywords: banking profitability; credit risk; interest rates